Potential and limitations of using sewage water for irrigation - Supriya; Behera, Biswaranjan; Verma, Parkash; Meena, Rajesh Kumar (Indian Farming, 2024)
In India, the largest user of water is the agricultural industry. Millions are being spent on irrigation projects to meet the water demand and lessen reliance on precipitation. Additionally, the problems with food security brought on by a growing population necessitate the need for cultivation in water-scarce areas. Even water of marginal quality should be taken into consideration as an alternative option in such conditions. Sewage effluent irrigation provides crops with water and nutrients. At the same time, it offers a convenient method of sewage disposal via land treatment, avoiding potential risks to human health and the environment from the unchecked flow of wastewater. Effluent is especially important in areas where there are few other water sources, and using it for irrigation frees up high-quality water for other applications.